Pengaruh Budaya Organisasi, Jenjang Karir Terhadap Kinerja Karyawan Dengan Kompensasi Sebagai Variabel Intervening (Studi Kasus Pada PT. Cahaya Lampung Selatan) - M Hafish Ferdiansyah; Durotun Nasikah; Nina Lelawati; Tyas Aisyah Nor Zureza (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the effect of organizational culture, career path on employee performance with compensation as an intervening variable. This research is quantitative, where quantitative research is research that uses data types that can be measured or calculated directly through measuring research variables using numbers. The data analysis technique used is the analytical method which includes instrument requirements testing, requirements analysis testing and Multiple Linear Regression testing. The results of the study show that Organizational Culture has a positive and significant influence on employee performance. Career path has a positive and significant impact on employee performance. Organizational Culture has a positive and significant influence on compensation Career path has a positive and significant influence on compensation